Use of the Whatsapp application in health follow-up of people with HIV: a thematic analysis - Ivana Cristina Vieira de Lima; Marli Teresinha Gimeniz Galvão; Samyla Citó Pedrosa; Gilmara Holanda da Cunha; Ana Karoline Bastos Costa (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To investigate the statements of people living with HIV during a health follow-up through the WhatsApp® application. Methods: A descriptive study, using a qualitative approach, was conducted with 26 people accompanied by two specialized care services for HIV/AIDS in Fortaleza, Ceará. Data were collected from September 2016 to February 2017, with participants' statements given during the online follow-up and submitted to thematic content analysis. Results: The following categories emerged: difficulties with treatment, antiretroviral dose delayed or missed, side effects, association between antiretroviral drugs and alcohol, use of dietary supplements and medicines, emotional changes, life habits, social rights, physical symptoms, and coping with and committing to with treatment. Conclusion: Follow-up over WhatsApp® improved access to health professionals, by providing an open and immediate communication channel.